Kesadaran Hukum Pengusaha Tahu Dalam Pengelolaan Air Limbah Roduksi Tahu Di Kota Kupang - Korin, Maria Henderika Arta; Pello, Jimmy; Fanggi, Rosalind A (Law Faculty, Nusa Cendana University, 2025)
In Indonesia, tofu is one of the most widely consumed foods by the Indonesian people with various variants circulating on the market such as tofu Sumedang, tofu content, tofu cakes and so on. This is what has resulted in the tofu industry experiencing significant development both from small and medium-scale industries Tofu processing will produce waste or there is waste that can be in the form of waste. Waste if not handled properly will cause pollution. In Indonesia, in fact, the development of the tofu industry is not followed by environmental awareness. The liquid waste is directly discharged into the riverbank so that it causes a decline and deterioration in the quality of river water, if the water is consumed it can cause health problems, because it creates a medium for the growth of disease germs or other germs that are detrimental to both the tofu product itself and the human body. Seeing this environmental phenomenon, legal awareness is the main highlight in it. Assessing a person's legal awareness, it is important to understand their knowledge, understanding, and acceptance of the law. A person's level of legal knowledge reflects their familiarity with legal principles and laws, while comprehension indicates their ability to interpret and apply this knowledge in practical situations. Additionally, acceptance indicates how well individuals accept legal norms and values in their social context. Together, these elements provide a comprehensive view of a person's legal awareness, influencing their behavior and interactions within the legal system.